Guaranteed time of pursuit for the strategy of parallel approach - Pashko, S.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
This paper is concerned with differential pursuit-evasion games, in which several players chase one, using the strategy of parallel approach. The strategy of evasion is constructed, and its optimality is proved. Optimal strategies of evasion are investigated. Linear programming problems, which specify the optimal strategies of evasion, are stated.